2021
DOI: 10.1002/anie.202104480
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Identification of Catalytically Active Sites on Oxygen‐doped Carbon Nanosheet to Decipher the High Activity for Electro‐synthesis Hydrogen Peroxide

Abstract: Electrochemical production of hydrogen peroxide (H 2 O 2 )t hrough two-electron (2 e À )o xygen reduction reaction (ORR) is an on-site and clean route.O xygen-doped carbon materials with high ORR activity and H 2 O 2 selectivity have been considered as the promising catalysts,h owever,t here is still alackofdirect experimental evidence to identify true active sites at the complex carbon surface.H erein, we propose ac hemicalt itration strategy to decipher the oxygen-doped carbon nanosheet (OCNS 900 )c atalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 68 publications
4
145
0
Order By: Relevance
“…[48] In the high-resolution O 1s spectra, the NC has two peaks at 531.7 and 533.1 eV corresponding to CO and COH, respectively (Figure 2e). [52,53] Both CO and COH groups are catalytic sites for ORR, but the product is H 2 O 2 via a 2e − pathway. [52,53] In addition, the high surface charge transfer resistivity of oxygen-containing functional groups results in high overpotentials in electrochemical reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[48] In the high-resolution O 1s spectra, the NC has two peaks at 531.7 and 533.1 eV corresponding to CO and COH, respectively (Figure 2e). [52,53] Both CO and COH groups are catalytic sites for ORR, but the product is H 2 O 2 via a 2e − pathway. [52,53] In addition, the high surface charge transfer resistivity of oxygen-containing functional groups results in high overpotentials in electrochemical reaction.…”
Section: Resultsmentioning
confidence: 99%
“…After careful deconvolution with the same standard rules, four distinct regions were identified. The four peaks included CO (531.0 eV), 4,5,33 C–O–C/OC–O (532.4 eV), 33,34 C–OH (533.7 eV), 29,33,34 and physically adsorbed H 2 O/O 2 (535.8 eV). 5,34 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The four peaks included CO (531.0 eV), 4,5,33 C–O–C/OC–O (532.4 eV), 33,34 C–OH (533.7 eV), 29,33,34 and physically adsorbed H 2 O/O 2 (535.8 eV). 5,34 Fig. S13† points out the deconvolution of the O 1s peaks of N-CBMC-500, N-XBMC-500, N-GBMC-500, and N-FBMC-500.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe or Co) to obtain optimal electronic and geometric structures. [14][15][16][17][18][19][20][21] More concretely, density functional theory (DFT) calculations suggested that co-doping of Fe and N in the form of possible FeN 4 sites on a graphitic substrate could be as active as Pt for O 2 adsorption and subsequent O]O bond breaking during the ORR. [22][23][24][25] In this sense, nitrogen-containing functional groups on a graphitic matrix also play a fundamental role in the performance and electronic conductivity of electrocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%